Development and implementation of an outcomes-based reading program for Barangay Dagatan reading center in Lipa City, Batangas - Diesta, Marianne P. (2018)
This project focuses on developing and implementing an outcomes-based reading program for the Barangay Dagatan Reading Center in Lipa City, Batangas. Moreover, it adopted the idea of the Outcomes-Based Reading Program developed by the California Library Association (CLA, 2018) with the aid of a Reading Blueprint designed for this reading program. The reading audience and program participants were selected based on the Chall's Stages of Developmental Reading and the Reading for Learning the New (Stage 3: 9 to 13 years old). The entire program was guided by a blueprint and detailed lesson plans documenting all the pre- and post-reading activities in each session.